Silencing PDCD4 Mediates TFEB Overexpression Promoting Proliferation, Migration and Invasion of Cervical Cancer HeLa Cells - Gao, Xing; Liang, Ziying; Yuan, Yanan; Liu, Wenbo (Indian Journal of Pharmaceutical Education and Research, 2024)
Aim/Background: Cervical cancer is a common gynecologic malignant tumor, its occurrence and development are related to genetic and environmental factors. Recent studies have shown that Programmed Cell Death 4 (PDCD4) and Transcription Factor EB (TFEB) plays crucial roles in the pathogenesis of cervical cancer. The interaction between PDCD4 and TFEB and their regulatory mechanism on cellular functions in cervical cancer have not been fully explored. Materials and Methods: Therefore, this study utilized the Hela cell line as a cervical cancer model to investigate the changes in TFEB expression levels and the proliferation, migration, invasion and EMT processes of cervical cancer cells through the silencing of PDCD4. Real-time quantitative PCR and Western blot were employed to assess the expression levels of PDCD4 and TFEB, while CCK-8, scratch assay, Transwell invasion assay and Western blot were used to evaluate changes in cell proliferation, migration, invasion capabilities and EMT processes. Results: The experimental results demonstrated that silencing PDCD4 significantly increased the expression level of TFEB. Simultaneously, silencing PDCD4 also significantly accelerated the proliferation rate of Hela cells, enhanced the cells’ migration, invasion capabilities and promoted the EMT processes. Further experimental results showed that silencing TFEB could partially reverse the promoting effects of PDCD4 silencing on cell proliferation, migration and invasion. In cervical cancer, silencing PDCD4 can lead to TFEB overexpression, thereby promoting the proliferation, migration and invasion of Hela cells. Conclusion: These findings provide crucial clues for the in-depth study of molecular mechanisms in cervical cancer and indicate that the PDCD4-TFEB pathway could potentially serve as a target for the treatment and prevention of this disease.
Keywords: Cervical Cancer; PDCD4; TFEB; Proliferation; Migration; Invasion